2021
DOI: 10.1172/jci.insight.141518
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide CRISPR/Cas9 screen in acute myeloid leukemia cells identifies regulators of TAK-243 sensitivity

Abstract: TAK-243 is a first-in-class inhibitor of ubiquitin-like modifier activating enzyme 1 that catalyzes ubiquitin activation, the first step in the ubiquitylation cascade. Based on its preclinical efficacy and tolerability, TAK-243 has been advanced to phase I clinical trials in advanced malignancies. Nonetheless, the determinants of TAK-243 sensitivity remain largely unknown. Here, we conducted a genome-wide CRISPR/Cas9 knockout screen in acute myeloid leukemia (AML) cells in the presence of TAK-243 to identify g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 54 publications
1
30
0
1
Order By: Relevance
“…For example, in a study of acute lymphoblastic leukemia, Autry et al (48) discovered that mutation of a previously unidentified gene, CELSR2, confers glucocorticoid resistance. Similarly, another CRISPR drug resistance screen found that BEND3 knockout confers resistance to antileukemia drug TAK-243 (49). Using this same strategy, CRISPR screening can also help explore the mechanism of resistance to immune cell killing.…”
Section: Crispr Screen Assay Strategiesmentioning
confidence: 95%
“…For example, in a study of acute lymphoblastic leukemia, Autry et al (48) discovered that mutation of a previously unidentified gene, CELSR2, confers glucocorticoid resistance. Similarly, another CRISPR drug resistance screen found that BEND3 knockout confers resistance to antileukemia drug TAK-243 (49). Using this same strategy, CRISPR screening can also help explore the mechanism of resistance to immune cell killing.…”
Section: Crispr Screen Assay Strategiesmentioning
confidence: 95%
“…A genome-wide Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) (CRISPR/Cas9) knockout screen in OCI-AML2 cells identifies the BEN domain containing 3 ( BEND3 ) as a regulator of TAK-243 sensitivity [ 179 ]. BEND3, a mediator for transcriptional repression, interacts with chromatin-modifying complexes and utilizes diverse strategies to induce repressive histones and to alter DNA methylation [ 180 ].…”
Section: Small Molecules In Amlmentioning
confidence: 99%
“…BEND3, a mediator for transcriptional repression, interacts with chromatin-modifying complexes and utilizes diverse strategies to induce repressive histones and to alter DNA methylation [ 180 ]. BEND3 knockout confers resistance to TAK-243 in vitro and in vivo [ 179 ]. TAK-243 treated BEND3 knockout cells exhibit little induction of proteotoxic stress (activating transcription factor 4 (ATF4), C/EBP Homologous Protein (CHOP), and phospho-c-Jun N-terminal kinase (p-JNK)), DNA damage (γH2AX), and apoptosis (cleaved Poly (ADP-ribose) polymerase (PARP)) markers [ 179 ].…”
Section: Small Molecules In Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…out upregulated the ATP-binding cassette super-family G member 2 (ABCG2) and decreased the intracellular levels of TAK-243. Thus, ABCG2 expression could be a predictor of TAK-243 sensitivity 12 .…”
Section: Protein Metabolismmentioning
confidence: 99%